PEMBUATAN MEDIA MOBILE LEARNING BERBASIS ANDROID UNTUK MATA PELAJARAN FISIKA KELAS XI SMA - Robika Alkadri; Yurnetti Yurnetti; Yohandri Yohandri (Universitas Negeri Padang, 2017)
This research aim to produce products such mobile learning media based Android on static fluid material is valid and practical.The type of this research is a development research This research procedure consists of seven stages including the potential and problems, data collection, product design validation design, revised design, testing product and the revision of the product. The subject of the research is that three of the lecturers as validators, two physics teachers, and 20 students. The data has been analyzed with descriptive analysis techniques. Research results are categorized as valid with the value of the average 86,64% , categorized very practical according to the teachers with the value of the average 90,33%, and categorized practical according to the students with the value of the average 85,92%.